The Effect of Reward And Punishment Systems on Improving the Quality of Health Services in Hospitals in Denpasar City: Literature Review - Rosita, Ni Putu Indah; Wijaya, I Wayan Septa; Wira, I.A Dwidyaniti; Suwedia, I Nyoman Gede Bayu Wiratama; Nijyoti, Nitya (Journal of Language and Health, 2024)
This study aims to examine the effect of reward and punishment systems on improving the quality of health services in hospitals, particularly in Denpasar City. Reward and punishment systems are crucial elements of human resource management that can motivate both medical and non-medical staff to enhance their performance. In the context of hospitals, these systems not only influence employee motivation but also have a direct impact on the quality of services received by patients. This research employs a literature review method, with data sourced from indexed national and international journals, textbooks, and related research reports. Data were collected through a literature search using databases such as, Scopus, and Google Scholar. Relevant articles were critically analyzed to identify key findings regarding the implementation of reward and punishment systems in the healthcare sector.The study reveals that an effective reward system can significantly boost employee motivation and improve service quality, while an appropriate punishment system helps maintain work discipline and prevents a decline in service standards. Achieving a balanced implementation of both systems is essential for optimal outcomes. Therefore, hospitals in Denpasar City are encouraged to adopt more effective reward and punishment systems to support the goal of enhancing health service quality. This research is expected to contribute to identifying the benefits and challenges of implementing such systems, as well as providing recommendations to improve their efficiency. Additionally, it aims to enrich the literature on quality management in healthcare services, particularly in the Indonesian context.